5-Quinolinecarboxaldehyde as a precursor of luminescent boron complexes: synthesis and optical studies. Issue 18 (4th May 2016) - Benelhadj, Karima; Retailleau, Pascal; Massue, Julien; Ulrich, Gilles
Graphical abstract: Highlights: Boron complexes based on N^N chelates (including BODIPYs) are presented. The X-ray structure of an original BODIPY dyes has been obtained and is described. The optical properties in solution- and solid-state are presented for all dyes. Abstract: 5-Quinolinecarboxaldehyde was used as a starting synthon to engineer a series of highly luminescent boron complexes based on BODIPY dyes or on original benzimidazole or phenanthroimidazole N^N chelates. For the BODIPY series, the 5-quinoline fragment was either introduced at the meso position of the π-conjugated core via a pyrrolic condensation or at the 3, 5 positions through Knoevenagel condensations. The N^N chelates were prepared with o -phenylenediamine or phenanthrenedione, respectively, followed by boron complexation. All these original complexes were characterized by structural and/or photophysical studies. The latter revealed absorption bands spanning the entire visible range and very intense emission bands upon photoexcitation. The photoluminescence quantum yields are very high, reaching up to unity, highlighting the potential use of these complexes as luminescent probes.